Planning for the Use of Crane Towers in High-Rise Multifamily Housing Projects - Yalan, B. S. (2024)
This research article proposes a compilation of the best practices necessary to improve the planning of the use of a crane tower in a construction site, evaluating as a case study, the SIDE Project, a high-rise multifamily housing with the incorporation of a POTAIN MC125 crane tower. The methodology applied is based on the analysis of the current planning processes of this machinery together with the problems presented by resident engineers, to then compile the good practices of the main crane tower suppliers in Peru. These were represented with the BIM modeling tool to study their effectiveness in the case study and capture the correct planning process. Finally, these practices were validated through expert judgment by specialists in this machinery. The results obtained in this research are mainly focused on the validation of the proposed good practices, receiving an approval of almost 100% by the experts in the proposed categories of the improvement processes. In addition, these collected practices received an 80% approval per category by the specialists when affirming that they are essential in the knowledge of resident engineers and builders.